2017
DOI: 10.1186/s12911-017-0419-3
|View full text |Cite
|
Sign up to set email alerts
|

Information needs for making clinical recommendations about potential drug-drug interactions: a synthesis of literature review and interviews

Abstract: BackgroundDrug information compendia and drug-drug interaction information databases are critical resources for clinicians and pharmacists working to avoid adverse events due to exposure to potential drug-drug interactions (PDDIs). Our goal is to develop information models, annotated data, and search tools that will facilitate the interpretation of PDDI information. To better understand the information needs and work practices of specialists who search and synthesize PDDI evidence for drug information resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 27 publications
(31 reference statements)
1
36
0
6
Order By: Relevance
“…The survey provided optional responses for resources, keywords, and study types that were identified from the team's prior research on the information needs of professionals who search and synthesize PDDI evidence [11]. Questions about PDDI information search were organized according to the range of PDDI topics important for clinical decision making recently published by Payne et al [29].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The survey provided optional responses for resources, keywords, and study types that were identified from the team's prior research on the information needs of professionals who search and synthesize PDDI evidence [11]. Questions about PDDI information search were organized according to the range of PDDI topics important for clinical decision making recently published by Payne et al [29].…”
Section: Methodsmentioning
confidence: 99%
“…A list of drug interaction experts was assembled starting with individuals our team has worked with on past PDDI projects, including the aforementioned information needs study [11] and a prior workgroup on PDDI evidence assessment. Experts were contacted and asked to provide names and contact information for other colleagues that would be appropriate to send the survey.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies focusing on specific subsets of individuals rely on other sources of data, such as electronic health records and published literature from clinical trials, where information about the individuals' medication intake is explicit (e.g., Akbarov et al, 2015;Zhou et al, 2016;Romagnoli et al, 2017). Harnessing social media for studying the effects of medications on specific cohorts would require developing systems that can automatically distinguish posts that express personal intake from those that do not.…”
Section: Introductionmentioning
confidence: 99%